Real time sensor integration system for all terrain robotic vehicle - Nagappan Nagajothi (2008)
This project aims to design and develop a software application system to process the multisensor dynamic data using a Real Time Operating System (RTOS) with C programming language for an All Terrain Robot Vehicle (ATRV).